2017
DOI: 10.1371/journal.pone.0181230
|View full text |Cite
|
Sign up to set email alerts
|

Potassium citrate prevents increased osteoclastogenesis resulting from acidic conditions: Implication for the treatment of postmenopausal bone loss

Abstract: The extracellular acidic milieu in bones results in activation of osteoclasts (OC) and inhibition of osteoblasts (OB) causing a net loss of calcium from the skeleton and the deterioration of bone microarchitecture. Alkalinization through supplementation with potassium citrate (K citrate) has been proposed to limit the osteopenia progression, even though its pharmacological activity in bone microenvironment is not well defined. We evaluated if K citrate was able to prevent the adverse effects that acidic milieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 62 publications
5
31
0
3
Order By: Relevance
“…For instance, potassium citrate (K citrate) is an alkaline compound used to increase urinary pH and prevent the precipitation of solutes in the urinary tract [ 26 ]. Previous in vitro studies demonstrated that K citrate is capable of preventing the adverse biological effects which a low extracellular pH induces on human bone cells [ 27 ]. A recent meta-analysis has shown that the daily administration of alkalizing supplements, including K citrate, for a time span ranging from 6 months to 2 years, led to a significant reduction in acid and calcium excretion, and a reduction in bone resorption, thus, suggesting a potential benefit to bone health [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, potassium citrate (K citrate) is an alkaline compound used to increase urinary pH and prevent the precipitation of solutes in the urinary tract [ 26 ]. Previous in vitro studies demonstrated that K citrate is capable of preventing the adverse biological effects which a low extracellular pH induces on human bone cells [ 27 ]. A recent meta-analysis has shown that the daily administration of alkalizing supplements, including K citrate, for a time span ranging from 6 months to 2 years, led to a significant reduction in acid and calcium excretion, and a reduction in bone resorption, thus, suggesting a potential benefit to bone health [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate is considered to decrease with acidosis under circumstances of increasing bone resorption; therefore, patients with urolithiasis with osteopenia or osteoporosis tend to have hypocitraturia [ 24 , 31 ]. In fact, some papers indicated that potassium citrate treatment reversed low BMD [ 32 , 33 ]. Such evidence suggests that awareness of urinary citrate levels is essential for evaluating stone development risk factors, including BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate is considered to decrease with acidosis under circumstances of increasing bone resorption; therefore, patients with urolithiasis with osteopenia or osteoporosis tend to have hypocitraturia [23,30]. In fact, some papers indicated that potassium citrate treatment reversed low BMD [31,32]. Such evidence suggests that awareness of urinary citrate levels is essential for evaluating stone development risk factors, including BMD.…”
Section: Discussionmentioning
confidence: 99%